Associations Between CAMKK1 Polymorphism rs7214723 and the Prognosis of Patients With Lung Cancer - Zhang, Haorui; Chen, Bocen; Zou, Zixiu; Feng, Jian; Li, Yutao; Wang, Yi; He, Xing; Xu, Chang; Wang, Haijian; Guo, Shicheng; Jin, Li; Li, Qiang; et al. (Frontiers in Oncology, 2021)
Background: The 5-year survival rate of patients with lung cancer in China is < 20%, and predicting their prog¬nosis is difficult. We investigated the association between a common non-synonymous single-nucleotide polymorphism (SNP) in the Ca2+/calmodulin-dependent protein kinase kinase 1 (CAMKK1) gene and the prognosis of patients with lung cancer. Methods: Genomic DNA was extracted from the blood samples of 839 patients with lung cancer recruited from Changhai Hospital (n = 536) and Taizhou Institute of Health Sciences (n = 352) and genotyped using the SNPscan technique. The association between patient prognosis and the Ca2+/calmodulin-dependent protein kinase 1 genotypic data was analyzed using a multivariate Cox proportional hazards model adjusted for multiple potential confounders. CRISPR/Cas9 gene-editing system was used to carry out point mutations at CAMKK1 rs7214723. Cell proliferation and migration ability were assessed by Cell Counting Kit-8, and cell scratch test, Annexin V-FITC apoptosis detection kit was used to detect cell apoptosis. Results: The CAMKK1 rs7214723 recessive CC genotype had significantly better overall survival (CC vs. TT + TC: adjusted hazard ratio = 0.78, 95% confidence interval [CI], 0.61-1.00, P = 0.049) than TT + TC genotypes. Stratified analyses showed that the CAMKK1 rs7214723 CC genotype and recessive CC had a significantly decreased risk of death in patients who were male, had a smoking history, or with stage III + IV cancer, compared with TT and TT + TC respectively. The rs7214723 recessive CC was also associated with a decreased risk of death relative to TT + TC in patients aged < 60 years (CC vs. TT + TC: adjusted hazard ratio = 0.59, 95% CI, 0.37-0.93, P = 0.024) and patients with squamous cell carcinoma (CC vs. TT + TC: adjusted hazard ratio = 0.65, 95% CI, 0.44-0.98, P = 0.038). Remarkably, CRISPR/Cas9-guided single-nucleotide editing demonstrated CAMKK1 rs7214723 T > C significantly inhibits cell proliferation and migration and promotes cell apoptosis. Conclusions: Ca2+/calmodulin-dependent protein kinase 1 SNP rs7214723 may be a significant prognostic factor for the risk of death among patients with lung cancer.